Deep subduction, melting, and fast cooling of metapelites from the Cima Lunga Unit, Central Alps. (1st July 2021) - Piccoli, Francesca; Lanari, Pierre; Hermann, Jörg; Pettke, Thomas
Abstract: The Cima Lunga unit in the Central Alps is dominated by quartzofeldspathic gneisses with subordinate mafic, ultramafic, and metacarbonate rocks. Only mafic and ultramafic lithologies were thought to preserve clear evidence of Alpine high‐ P metamorphism. This led to the questions of whether the different rock types were subducted and exhumed as a coherent unit or underwent different pressure–temperature ( P – T ) histories. New petrological and geochemical data from a metapelite associated with garnet peridotite from Cima di Gagnone (Cima Lunga unit, Switzerland) were obtained using major and trace element mapping. Complex zoning patterns in garnet and white mica are observed. In particular, high Ti content in phengite and increasing P, Zr, and HREE contents in pyrope‐rich garnet indicate that this metapelite underwent high‐ P and high‐ T ( HP–HT ) metamorphism involving fluid‐fluxed partial melting. A P–T path is reconstructed by combining textural analysis with petrological–geochemical data and thermodynamic simulations. We show that the mineral record preserves an evolution from prograde to HP–HT peak conditions (2.7 ± 0.1 GPa and 800℃) followed by near‐isobaric cooling ( 2.5 GPa and 700–750℃) prior to decompression (1.0 GPa and 620℃). The reconstructed P – T path suggests that the studied metapelites were subducted to depths where the slab gets heated by proximity to asthenospheric mantle related to slab break‐off. This heating resulted in the dehydration of chlorite‐ to garnet peridotite and the liberated fluids triggered partial melting in the associated metapelites, which might have favoured the fast exhumation of the entire Cima Lunga unit. Metapelites and garnet peridotite from Cima di Gagnone underwent a common prograde to peak and retrograde P – T path without significant tectonic pressure difference between the different lithologies, and deviation from lithostatic pressure is excluded. Lastly, the peak metamorphic conditions of metapelite from Cima di Gagnone are comparable with P – T estimates of ultramafic lithologies from the southern Adula nappe and the Dascio Bellinzona zone, thus opening new scenarios for the geodynamic interpretation of the Central Alps.